Comparison of Physico-Chemical Properties Between Two Varieties of Peanut (Arachis hypogaea L.) Seed Oil from Pakistan - Cecil, Farhan; Anwar, Farooq; Ali Shahid, Shaukat; Ahmad, Naveed (Asian Journal of Chemistry, 2013)
The present research work was aimed to evaluate and quantify the physico-chemical attributes between two varieties of peanut (Arachis hypogaea L.) seed oil. The oil yield from two locally grown peanut varieties namely var. Banki and 334, using Soxhelt extraction method, was found to be 34.62 and 32.43 %, respectively. The seed kernel of the peanut varieties tested contained fiber, ash and protein 3.70, 3.90, 2.30, 2.50, 24.62 and 26.19 %, respectively. The physico-chemical attributes of the extracted oils were found to be refractive index (40 ºC) 1.4623, 1.4536; free fatty acids 2.65, 3.55 % as oleic acid; peroxide value 2.50, 3.50 meq/kg; iodine value 93.45, 91.96 g of I/100 g; saponification value 193.20, 188.00 mg of KOH/g of oil; unsponifiable matter 1.20, 1.50 %; p-ansidine value 1.54, 1.87, respectively. The colour of the tested oils varied from 1.42-1.51R + 14.00-15.00 Y. The seed oils mainly contained g-tocopherol (709.1-712.2 mg/kg) followed by a-tocopherol (173.9-193.2 mg/kg) and d-tocopherol (7.1-8.4 mg/kg). The peanut seed oils were characterized by high level of oleic acid (46.10-47.70 %) followed by linoleic acid (27.60-30.40 %), palmitic acid (12.70-13.50 %) and stearic acid (5.10-5.70 %). Generally, most of the physico-chemical attributes of the peanut seed oils varied insignificantly between the two varieties tested.